2018
DOI: 10.1055/s-0043-125445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depression and Psychosocial Treatment on Heart Rate Variability in Patients with Type 2 Diabetes Mellitus: An Exploratory Analysis Based on the HEIDIS Trial

Abstract: Depression was not directly associated with cardiac autonomic control in this sample, but MBSR training may have positively influenced HR and HRV. In advanced diabetes, somatic and behavioral parameters seem to be more predictive than depression for the course of autonomic functioning, but the pathways remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The index ranges from 0.25 to 1.0, with indices below 0.5 being no depression; 0.5–0.59 being mild to mild depression, 0.60–0.69 being moderate to severe depression; and over 0.70 being severe depression. Zung tested the reliability and validity of the SDS: its internal consistency was satisfactory, with split correlations of 0.73 (1973) and 0.92 for the odd-even items (1986), with high and moderate correlations with scores on the Beck Depression Questionnaire, the Hamilton Depression Inventory, and the Matrix Metalloproteinase “d” subscale ( Zimmermann-Schlegel et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The index ranges from 0.25 to 1.0, with indices below 0.5 being no depression; 0.5–0.59 being mild to mild depression, 0.60–0.69 being moderate to severe depression; and over 0.70 being severe depression. Zung tested the reliability and validity of the SDS: its internal consistency was satisfactory, with split correlations of 0.73 (1973) and 0.92 for the odd-even items (1986), with high and moderate correlations with scores on the Beck Depression Questionnaire, the Hamilton Depression Inventory, and the Matrix Metalloproteinase “d” subscale ( Zimmermann-Schlegel et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that depressive symptoms and glucose metabolism in middle-aged and elderly patients improve through general psychological support and other interventions ( Fiocco et al, 2013 ; Zimmermann-Schlegel et al, 2019 ). This study implemented psychological interventions for middle-aged and elderly patients in the following areas: first, behavioral therapy to intervene in diabetic diet and lifestyle changes so that patients can adapt to long-term treatment and strict dietary control as soon as possible; second, supportive therapy and coping guidance to improve the coping skills and social support system of middle-aged and elderly patients; third, relaxation therapy to relieve stress caused by tension-induced blood glucose fluctuations; fourth, cognitive therapy to reduce depression.…”
Section: Introductionmentioning
confidence: 99%
“…Although depression is an established risk factor for morbidity and early mortality, 16 little is known about the association between depression and HRV among people with diabetes. 17,18 An observational study has shown a mediating effect of depression in association between parasympathetic activation and HbA 1c among people with type 2 diabetes, 18 while another study in people with type 2 diabetes found no association between depression and HRV. 17 Studies in people with type 1 diabetes are still lacking.…”
Section: What's New?mentioning
confidence: 99%
“…17,18 An observational study has shown a mediating effect of depression in association between parasympathetic activation and HbA 1c among people with type 2 diabetes, 18 while another study in people with type 2 diabetes found no association between depression and HRV. 17 Studies in people with type 1 diabetes are still lacking.…”
Section: What's New?mentioning
confidence: 99%
See 1 more Smart Citation